High-Resolution Coproecology: Using Coprolites to Reconstruct the Habits and Habitats of New Zealand’s Extinct Upland Moa (Megalapteryx didinus) - Wood, Jamie R.; Wilmshurst, Janet M.; Wagstaff, Steven J.; Worthy, Trevor H.; Rawlence, Nicolas J.; Cooper, Alan (PloS one, 2012)
Contributes to the knowledge of moa diet and ecology by reporting the results of a multidisciplinary study of 35 coprolites from a subalpine cave (Euphrates Cave) on the South Island of New Zealand. Identifies at least 67 plant taxa from the coprolites, including the first evidence that moa fed on the nectar-rich flowers of New Zealand flax (Phormium) and tree fuchsia (Fuchsia excorticata). Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.